Changes in Gender Power Dynamics in Congo - Doe, John (International Journal of Gender Studies, 2023)
Purpose: The purpose of this study was to explore the changes in gender power relations among the people of Congo. Methodology: The study adopted a desktop methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low-cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Results: The results revealed that there exist conceptual and contextual gaps relating to the study on the changes in gender power relations among the people of Congo. Preliminary empirical review reveals that Gender power relations underwent changes emanating from socio-economic and dynamics to fit within the capitalist production system. Unique Contribution to Theory, Practice and Policy: Gender role theory and social construction theory may be used to categorize the key work design factors which may relate to gender power relations among the people of Congo. The results of this research will form the basis for further research to investigate into the areas of gender power relations.